अतगाम - Kunu Baskey (Adibasi Socio-Educational & Caltural Association Kumrasole Dumuria, 2004)
This is a Geagraphy book written in Santali.
Atgam (A Geography In Santhali)
Keywords: Santali; Geography; Santali